Strengthening the core in calculus: differentiation and integration / Norshuhada Samsudin, Nur Azimah Idris and Noor Azizah Mazeni - Samsudin, Norshuhada; Idris, Nur Azimah; Mazeni, Noor Azizah (Unit Penerbitan JSKM, 2020)
Calculus plays a vital role in mathematics and is the important branch in Applied Mathematics. Calculus covers from limit, functions, derivatives, and integral till infinite series. Understanding key concepts in Algebra and Trigonometry is needed to have a better comprehension in Calculus. As Calculus is widely applied in the field of engineering, sciences and economics, it is essential for students to learn this subject in schools and higher education institutes. Nevertheless, students struggle and perceive Calculus as a hard and difficult subject where they often misunderstood the concept of calculus (Tarmizi, 2010). Students generally have difficulties in solving problems with limits, derivative and integral (Siti Fatimah, 2019). Therefore, this article serves as a tool for students to grasp the heart of calculus which consists of differentiation and integration. It also tackles on basic algebra and trigonometry, definitions as well as techniques of differentiation and integration.